The role of social support in the mental health of primiparous mothers postpartum: A systematic review - Savitri, Wewet; Irwandy, Irwandy; Wahiduddin, Wahiduddin; Mallongi, Anwar (Edelweiss Applied Science and Technology, 2026)
The postpartum period is a critical transition for primiparous mothers and is associated with an increased risk of mental health problems, particularly depression and anxiety. This systematic review aims to examine the role of social support in maintaining the mental well-being of first-time mothers. The review was conducted following PRISMA guidelines by analyzing articles published between 2015 and 2025 from PubMed, SpringerLink, ScienceDirect, and Google Scholar using relevant keywords. A total of 20 eligible studies were included in the analysis. The findings indicate that partner support is the most effective form of social support, significantly reducing depressive and anxiety symptoms while enhancing maternal self-efficacy and mother-infant bonding. Support from family members, friends, and community networks also contributes to stress reduction, decreased loneliness, and better adaptation to the maternal role. Additionally, adequate social support was associated with improved breastfeeding outcomes. In conclusion, social support, particularly from partners, plays a vital role in protecting the mental health of primiparous mothers. These findings emphasize the importance of strengthening family- and community-based support interventions to promote maternal mental well-being during the postpartum period. This study did not require ethical approval as it involved secondary data, and no conflicts of interest were declared.